2021
DOI: 10.1177/87551233211056995
|View full text |Cite
|
Sign up to set email alerts
|

Research-to-Resource: Applying a Self-Care Framework to Music Education

Abstract: Self-care is a topic that has gained traction among helping professionals. It is considered a preventive health care measure used to promote physical and mental health as well as personal well-being. In this article, I use a self-care framework created for social workers and adapt it to music educators with the intention of aiding music teachers in practicing and maintaining their own self-care. The self-care framework is categorized into two dimensions—personal and professional self-care—which each contains v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As a result of research analysis (Miksza et al, 2021;Rickers, 2021;Zabanal, 2021), it is concluded that music teachers should take care of their personal and professional well-being because the risk of a high level of stress and negative well-being is greater than the population average. As a consequence of paying attention to personal well-being, the music teachers improve their effectiveness and provide a positive learning environment for students.…”
Section: The Stress and Well-being Of Music Teachers And Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of research analysis (Miksza et al, 2021;Rickers, 2021;Zabanal, 2021), it is concluded that music teachers should take care of their personal and professional well-being because the risk of a high level of stress and negative well-being is greater than the population average. As a consequence of paying attention to personal well-being, the music teachers improve their effectiveness and provide a positive learning environment for students.…”
Section: The Stress and Well-being Of Music Teachers And Studentsmentioning
confidence: 99%
“…What should be done to make music teachers and students feel good while teaching and learning in today's changing environment? Researchers determined that teachers should be compassionate (Kaschub, 2020), improve their knowledge of how to take care of their well-being (Zabanal, 2021), achieve work-life balance (Rickers, 2021), and play music or listen to music (Merve et al, 2021). On the one hand, music teachers gain more energy by being excited about what they are doing (Zabanal, 2021), but on the other hand, they should manage work time and define tasks to reach a work-life balance (Rickers, 2021).…”
Section: The Stress and Well-being Of Music Teachers And Studentsmentioning
confidence: 99%
See 1 more Smart Citation